2020
DOI: 10.1192/bjp.2019.265
|View full text |Cite
|
Sign up to set email alerts
|

The effects of once- versus twice-weekly sessions on psychotherapy outcomes in depressed patients

Abstract: BackgroundIt is unclear what session frequency is most effective in cognitive–behavioural therapy (CBT) and interpersonal psychotherapy (IPT) for depression.AimsCompare the effects of once weekly and twice weekly sessions of CBT and IPT for depression.MethodWe conducted a multicentre randomised trial from November 2014 through December 2017. We recruited 200 adults with depression across nine specialised mental health centres in the Netherlands. This study used a 2 × 2 factorial design, randomising patients to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 24 publications
(33 reference statements)
1
71
0
Order By: Relevance
“…In a recent meta-analysis summarizing data from 366 trials, Cuijpers and colleagues reported that "[psychotherapy] effect sizes are small in childhood, become larger in adolescents, and grow further in early adulthood, before decreasing to more modest effect sizes in the rest of the adult population" (Cuijpers et al, 2020). Although the authors do not report CBT-specific data, a substantial proportion of the studies analyzed were CBT studies, and the age effects did not appear to vary across treatment modalities.…”
Section: Agementioning
confidence: 99%
“…In a recent meta-analysis summarizing data from 366 trials, Cuijpers and colleagues reported that "[psychotherapy] effect sizes are small in childhood, become larger in adolescents, and grow further in early adulthood, before decreasing to more modest effect sizes in the rest of the adult population" (Cuijpers et al, 2020). Although the authors do not report CBT-specific data, a substantial proportion of the studies analyzed were CBT studies, and the age effects did not appear to vary across treatment modalities.…”
Section: Agementioning
confidence: 99%
“…The second trial is the FreqMech trial (n = 200), which was conducted between November 2014 and January 2018, randomizing depressed patients into different session frequencies of CBT and IPT (i.e., CBT weekly (n = 49), CBT twice weekly (n = 49), IPT weekly (n = 55), IPT twice weekly (n = 47)). A higher session frequency led to more reduction of depression, but there were no average group differences between CBT and IPT (Bruijniks et al, 2020). Although the studies used the same treatment protocols for CBT and IPT (i.e., only the session frequency differed), the studies differed in a number of other important aspects.…”
Section: Study Design and Clinical Trial Datamentioning
confidence: 99%
“…In the STEPd trial patients received weekly sessions with some flexibility to schedule appointments less often then weekly. Treatment competence was rated good to excellent in 83-90% of the videotapes from the STEPd trial (Lemmens et al, 2015) and poor to excellent in the FreqMech trial (only 12-16% of the video-tapes were rated good-excellent; Bruijniks et al, 2020) using the Cognitive Therapy Scale for CBT (Dobson et al, 1985), and the short version of the IPT Adherence and Quality Scale for IPT (Stuart, 2011). 1 In both trials, there were significant differences in therapy-specific behaviour, with higher CBT-specific behaviour in CBT as compared to IPT, and higher IPT-specific behaviour in IPT as compared to CBT (rated with the Collaborative Study Psychotherapy Rating Scale version 6; Hollon et al, 1988).…”
Section: Treatmentsmentioning
confidence: 99%
“…Higher session frequency in the first 3 months of treatment is associated with faster improvement and recovery (Tiemens et al, 2019). Further, patients randomized to receive twice-weekly sessions experienced greater depression reductions than those offered once-weekly therapy (Bruijniks et al, 2020).…”
Section: Treatment Need Not Occur Once-weeklymentioning
confidence: 98%